Traineeships as a form of improvement of Geoinformation students' professional competences on the labour market - Winowski, Marcin (Journal of Education, Health and Sport, 2017)
The today's labour market poses serious challenges to be faced by higher education graduates. Job applicants' specialised substantial knowledge, well-developed interpersonal competencies and - not rarely - professional experience are the essential features which are mostly appreciated by employers. Inexperienced 'fresh' higher education graduates often lack these requisite abilities and skills, which makes them hard to find their way in the labour market and get their dream job. In 2015 at the Adam Mickiewicz University - thanks to the initiative of two faculties - the "Bridge to the labour market" traineeship program was launched, which was attended by last-year students. The project was funded under the 'Human Capital' Operational Program, Priority IV Higher education and science. The article shows the key assumptions and results of the project.